2009
DOI: 10.1007/s11665-008-9267-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Capacitance Characteristics of C60, C70, and La@C82

Abstract: Fullerenes and their derivatives are promising materials for supercapacitor devices due to their unique nanostructure that combines the reversible redox charge storage with the high surface area. In this article, the reversible redox charge storage of C 60 , C 70 , and La@C 82 in liquid ammonia solution is reported. An electrochemical analysis of these species using cyclic voltammetry is presented in conjunction with the theoretical interpretation. The relative magnitudes of transfer coefficients, which repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The properties of these fullerenes are relevant for the potential processing of materials used for supercapacitor devices where charge storage and capacitance characteristics must be quantified. 22 The ability of C 60 nanoparticles, mechanochemically embedded in different solubilising agents, to protect mammalian cells against in vitro cytotoxicity of the biologically relevant highly reactive free radical nitric oxide was investigated. The cytoprotective action of C 60 nanoparticles was not mediated by direct interaction with nitric oxide, but rather through neutralisation of mitochondria-derived superoxide radical anion.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation
“…The properties of these fullerenes are relevant for the potential processing of materials used for supercapacitor devices where charge storage and capacitance characteristics must be quantified. 22 The ability of C 60 nanoparticles, mechanochemically embedded in different solubilising agents, to protect mammalian cells against in vitro cytotoxicity of the biologically relevant highly reactive free radical nitric oxide was investigated. The cytoprotective action of C 60 nanoparticles was not mediated by direct interaction with nitric oxide, but rather through neutralisation of mitochondria-derived superoxide radical anion.…”
Section: Production Separation and Properties Of Fullerenesmentioning
confidence: 99%
“…182 The ESR technique has been employed to systematically provide direct evidence that Gd@C 82 (OH) 22 , C 60 (OH) 22 , and C 60 (C(COOH) 2 ) 2 nanoparticles can effectively scavenge different types of free radicals/ROS. 183 The possible scavenging activity of NO, by the hydroxylated fullerene derivative C 60 (OH) 22 and malonic acid derivative C 60 (C(COOH) 2 ) 2 were investigated using primary rat brain cerebral microvessel endothelial cells. 184 It indicated that C 60 (C(COOH) 2 ) 2 nanoparticles possess a novel ability of selectively entering oxidation-damaged cerebral endothelial cells, rather than normal endothelial cells and then protecting them from apoptosis.…”
Section: Advanced Materialsmentioning
confidence: 99%
“…It would be very interesting to create novel hybrid nanomaterial composed of graphene and fullerene, as it is expected that binding of fullerenes to graphene surface should not only increase the capacity of resulting hybrid nanomaterial (Ma et al 2015;Cerón et al 2019) but also provide adequate stability and prevent restacking of graphene sheets (Wang et al 2009). Reports on not only performance comparison for capacitors based on C 60 or C 70 fullerenes (Tran et al 2009) but also on energy storage application of C 70 and its derivatives are scarce (Bairi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fullerenes and their derivatives are considered promising as electrodes of supercapacitors because of their reversible redox charge storage and large surface areas (1100-1400 m 2 g -1 [35]. However, reports on supercapacitors based on fullerenes or fullerenes combined with other carbon allotropes are limited in the literature mainly owing to the low specific capacitances [13].…”
Section: Fullerene-based Supercapacitorsmentioning
confidence: 99%